Risk Factors of Periprosthetic Infection in Patients with Tumor Prostheses Following Resection for Musculoskeletal Tumor of the Lower Limb - Fujiwara, Toshifumi (J Clin Med, 2020)
Tumor prostheses for the lower limb following resection of musculoskeletal tumors is useful limb salvage management; however, as compared with routine total joint replacement, an increased incidence of deep periprosthetic infection of tumor prosthesis has been observed. The risk factors for periprosthetic infection of tumor prosthesis remain unclear. This study examines the risk factors and outcomes of periprosthetic infection. This was a retrospective observational study including 121 patients (67 males and 54 females) who underwent tumor prosthesis of the lower limb after resection of musculoskeletal tumors between 1 January 2000 and 30 November 2018. Among a total of 121 tumor prostheses, 7 were total femurs, 47 were proximal femurs, 47 were distal femurs, and 20 were proximal tibias. The incidence of postoperative infection and its risk factors were analyzed. Forty-five patients (37%) had osteosarcoma, 36 patients (30%) had bone metastasis, and 10 patients (8%) had soft-tissue tumors invading the bone. The mean operating time was 229 min, and the mean follow-up duration was 5.9 years. Deep periprosthetic infection was noted in 14 patients (12%). In the multivariate analysis, the risk factors for postoperative infection were identified as being male (hazard ratio [HR], 11.2316; p = 0.0100), soft-tissue tumor (HR, 52.2443; p = 0.0003), long operation (HR, 1.0056; p = 0.0184), and radiotherapy (HR, 6.5683; p = 0.0476). The incidence of periprosthetic infection in our institution was similar to that of previous reports. Patients undergoing tumor prosthesis of the lower limb who were male, had a soft-tissue tumor, were predicted to have a long operation, and who underwent radiation, had an increased possibility of postoperative infection.